11.30 Comparison of fixed high dose with variable low dose rituximab in neuromyelitis optica spectrum disorders. Issue 12 (14th November 2019) - Kelly, Patricia; Whittam, Daniel; Linaker, Samantha; Mutch, Kerry; Karthikeayan, Venkatraman; Huda, Saif; Jacob, Anu
Abstract : Introduction: Rituximab is an effective treatment for neuromyelitis optica spectrum disorders (NMOSD) but the ideal dosing regimen is unknown. This study compares a standard fixed dosing regimen (2 g 6-monthly) with a lower variable dosing regimen (2 g induction, then 1–2 g on repopulation of CD19+ B-cells to ≥1% of circulating lymphocytes, tested monthly). Method: Retrospective review of all rituximab-treated adult NMOSD patients who had at least 6months relapse-free follow-up from treatment initiation (n=52). Rituximab dosing fell into four groups: Purely fixed dosing (n=13), purely variable dosing (n=18), fixed then variable dosing (n=18), other (n=3). Results: Median annualized relapse rate (ARR) was not significantly different between these groups. Pooled analysis of all fixed dosing (n=31, median duration 25 months) versus all variable dosing (n=36, median duration 38 months) showed median and mean ARRs of 0.00 and 0.10 in both groups. Patients on fixed dosing received a median 3.9 infusions/year; those on variable doing received only 1.5 infusions/year. Conclusion: Variable dosing of rituximab with B-cell monitoring appears as effective as fixed dosing with lower cumulative drug doses. This approach led to reduced costs, increased patient convenience and has the potential for reducing side effects.